EFFECT OF LEAD AND CADMIUM ON HEMATOLOGICAL PARAMETERS AND LIVER ENZYMES ACTIVITY IN Luciobarbus xanthopterus (Heckel, 1843) IN TIGRIS River - Z. M. Abbas; L. M. Abbas; J. S. AL-Sariy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The current study was conducted in two different sites , these, sites S1 and S2 were located before and After Al- Kut Barrier respectively at Tigris River middle of Iraq. This study focused on evaluation the effect of lead Pb and cadmium Cd on Guttan, Luciobarbus xanthopterus for the period from January to September 2021. Monthly, some of water qualities were measured. The values for Water temperature ranged between 6.2 to 20.6 ºC , DO2 were recorded values between 11.16 to 6.12 mg /l. , BOD5 values were showed values between 1.03 to 3.42, water turbidity values of 11.7 to 72.4 NTU, The pH water values were ranged between 6.4 to 7.7 at sites S1 and S2 respectively. Lead and Cadmium concentration of water at Tigris River were 0.010 at S1 to 0.513 µg /l at S2 for Lead .Where’s, cadmium concentration ranged between 2.53 at S1 to 11.573 µg /l at S2. At the present study, some of Liver enzymes activity for Guttan were measured. These fishes blood enzymes AST, ALT and ALP were recorded a value of 51.2, 15.53 and 8.98 U/l respectively at S1. And a values of 410, 47.52 and 72.89 U/l for the same enzymes respectively at S2.The conclusion of current study showed that water quality at S1was suitable for Guttan, as well as, Fishes were best healthy than these at S2.